Avaliação ecotoxicológica do sedimento a montante e a jusante da barragem do Ribeirão João Leite – Goiânia/GO - Rios, Kelly Cristine Rodrigues Constantino (2013)
The aquatic environmental quality monitoring is the way to detect changes in their essential features to life. The Ribeirão João Leite, located in the State of Goiás, it highlights the need for constant monitoring, seen its socio-economic importance, the accelerated and disordered growth that plagues the region, land use focused mostly to agriculture and livestock and especially its use to the water bus intended for public supply. Searches for the water column are often conducted developed to the site. However reviews focused on the quality of sediment in this environment are nonexistent, despite the importance of such compartment. The sediment has been shown as an important indicator of the health of aquatic ecosystems, since most contaminants of a basin river system are washed down into the aquatic systems and can be deposited in this compartment. In this way, based on the importance of sediment to the water quality, the main objective of this work was to evaluate the quality of the sediment of the River João Leite, upstream and downstream of a dam public supply, through ecotoxicological of sediments compared to the physical-chemical parameters in two seasons (dry and rainy season). The work presented here addresses important aspects when assessing sediment quality, through four articles divided into chapters. The first chapter is the characterization of the space-exploratory study area considering its features and the relationship between the type of soil, polluting sources and composition of the sediment. The second chapter corresponds to a physical-chemical characterization of the sampled site as well as the lifting of a possible contaminant (metals), and its potential for bioavailability. The third and fourth chapters are focused on ecotoxicological assessment, where the organisms-test Ceriodaphnia dubia were used in the third chapter and Branchiura sowerbyi in the fourth chapter. The results of this study point to the need to deploy evaluations focused on the sediments of the River João Leite as everyday monitoring, since the site has problems of degradation, with high degree of anthropization, together with the lack of soil management and conservation. To the metals contaminants, the environment revealed toxicity unlikely to uncertain. And toxicity tests with the test organisms, Ceriodaphnia dubia and Branchiura sowerbyi, revealed in some cases acute effect, but mostly chronic effect and possible effect hormetc, which are evidence of an environment that is suffering disruptions, whether from metals or is by the performance of other contaminants as non-ionic organic compounds, such as pesticides, widely used in the region. Thus, this category of work being pioneered in the region is evident the need for further research aimed at this type of compartment (sediment) and especially that such studies become part of regular monitoring aimed to ensure water quality of the River João Leite.